The influence of Price, Innovation, and Brand Image on Purchase Decision - Alwa Pascaselnofra Amril (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2021)
This study aims to determine how big the influence of price, innovation and brand image partially or jointly on purchasing decisions. The method of data collection was through questionnaires with a sample of 95 students from the Faculty of Economics, Universitas Negeri Padang, Department of Management. The method used is multiple regression analysis. The results of the correlation analysis test show that there is a significant relationship between price, innovation and brand image on purchasing decisions for LENOVO products. The results of the multiple linear regression analysis were obtained: (a) There is a negative and significant effect between price on purchasing decisions, as evidenced by the value of t-statistic < t-table (-2.627 < 1.986). (b) There is a positive and significant influence between innovation on purchasing decisions, as evidenced by the value of t-statistic > t-table (4.494 > 1.986). (c) There is a significant influence between brand image on purchasing decisions, as evidenced by the value of t-statistic > t-table (4.631 > 1.986). Then based on the joint hypothesis test (F test) it can be seen that the value of F-statistic > F-table (21.902 > 2.70). So the author concludes that price, innovation and brand image have a significant effect on purchasing decisions and the result of Determination (R2) the value is 0.419 this shows that the contribution of the influence of the variables studied in this study is 41.9% and the remaining 58.1% is influenced by the variables others outside of this study.